Ultrasonic-driven electrical signal-iron ion synergistic stimulation based on piezotronics induced neural differentiation of mesenchymal stem cells on FeOOH/PVDF nanofibrous hybrid membrane. (September 2021) - Zhang, Ruitong; Han, Shuwei; Liang, Linlin; Chen, Yuke; Sun, Baojun; Liang, Na; Feng, Zhichao; Zhou, Hengxing; Sun, Chunhui; Liu, Hong; Wang, Jingang
Abstract: Neural stem cells (NSCs) are thought to be the best seed cells for neurodegenerative diseases therapy due to their potential to differentiate into either neurons or glial cells. However, the lack of resources for autologous NSCs prohibits their clinical applications. Although mesenchymal stem cells can be conveniently obtained from patients, neural differentiation is difficult to be realized, which becomes the great challenge for stem cell-based neurodegenerative diseases therapy. Herein, we report a novel method to induce neural differentiation of rat bone-marrow-derived mesenchymal stem cells (rBMSCs) based on piezotronics without any neural inducing factors (NIFs). In this work, a hybrid nanofibrous membrane was prepared by assembling a layer of FeOOH nanorods on the surface of polyvinylidene fluoride (PVDF) electrospun nanofibers. Under ultrasonic irradiation, piezoelectric-driven localized electric potential and electrical-driven iron ion (Fe 3+ ) release based on piezotronics induced neural differentiation of rBMSCs cultured on the surface of these membranes. Genetic and molecular assays on the differentiated cells demonstrated that the synergistic effects of electrical signals and iron ion release induced the differentiation of rBMSCs into neurons (γ-aminobutyric acid (GABA)ergic, cholinergic and aminergic neurons) without any NIFs. Intracellular calcium imaging experiments showed that the differentiated cells generated fast peaking spontaneous [Ca 2+ ]i-transients under the effects of neurotransmitters, especially GABA, indicating that rBMSCs-derived neurons had neuronal function. This study provides a novel strategy for inducing neural differentiation of rBMSCs via wireless stimulation with piezotronic effect, which is of great significance in clinical and neural tissue engineering. Graphical Abstract: ga1 The localized electrical signals derived from ultrasound-driven PVDF and the piezoelectric potential-accelerated controlled release of iron based on piezotronics can cause the differentiation and development of rBMSCs into neurons. Highlights: A novel strategy for inducing neural differentiation based on piezotronics. Neural differentiation via wireless stimulation without neural inducing factors. Synergistic effects of electrical signals and Fe 3+ release under ultrasound. The differentiation of rBMSCs into functional neurons.